(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
In the literature, two competing viewsstand out with respect to the position of employee well-being at work in HRM -performance research. Employee well-being is described here according threedimensions: happiness, health, and relationships. This review examines which ofthe competing perspectives, ‘mutual gains’ or ‘conflicting outcomes’ is moreappropriate to describe the role of these three employee well-being componentsas found in empirical research. It covers 41 studies published from 1995 to2008. Based on the quality of the studies and the consistency of the studyfindings, it is concluded that employee well-being in terms of happiness andrelationships function as mutual gain with performance. Health-relatedwell-being, however, seems to function as conflicting outcome with performance.Directions for future research and theoretical development are suggested.